Environmental Impact Assessment of the Industrial Estate Development Plan with the Geographical Information System and Matrix Methods. (5th January 2012) - Ghasemian, Mohammad; Poursafa, Parinaz; Amin, Mohammad Mehdi; Ziarati, Mohammad; Ghoddousi, Hamid; Momeni, Seyyed Alireza; Rezaei, Amir Hossein
Abstract : Background . The purpose of this study is environmental impact assessment of the industrial estate development planning. Methods . This cross-sectional study was conducted in 2010 in Isfahan province, Iran. GIS and matrix methods were applied. Data analysis was done to identify the current situation of the region, zoning vulnerable areas, and scoping the region. Quantitative evaluation was done by using matrix of Wooten and Rau. Results . The net score for impact of industrial units operation on air quality of the project area was (−3). According to the transition of industrial estate pollutants, residential places located in the radius of 2500 meters of the city were expected to be affected more. The net score for impact of construction of industrial units on plant species of the project area was (−2). Environmental protected areas were not affected by the air and soil pollutants because of their distance from industrial estate. Conclusion . Positive effects of project activities outweigh the drawbacks and the sum scores allocated to the project activities on environmental factor was (+37). Totally it does not have detrimental effects on the environment and residential neighborhood. EIA should be considered as an anticipatory, participatory environmental management tool before determining a plan application.